Inhibiting Factors in the Administration of Education (Senior High School) in Kepulauan Riau Province - Auly Fikry; Endang Larasati; Ida hayu Dimawati (Program Pascasarjana Universitas Negeri Makassar, 2019)
The policy for transfer of authority to manage high schools from district or city government to provincial governments, in its implementation, experienced various kinds of obstacles. As in the Riau Islands province, with the number of islands reaching 394 inhabited islands scattered throughout the Riau Islands region, the transfer of authority from the district / city to the province will have some changes that must be made. The purpose of this study is to examine the management of high school education in the Riau Archipelago. The research method used is qualitative, data collection is done through interviews and observations. The results showed that there were two factors which became obstacles in the management of senior high school education in the Riau Islands, namely the geographical environment and the national education system. The results showed that the geographical environment of the archipelago which has a 95% sea area had several impacts in running.